Consistency of information on the provision of water fluoridation in Brazil - Anna Laura Santos Doalto; Lorrayne Belotti; Camila de Moraes Paulino; Paulo Frazão (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: This study aimed to assess the consistency of data regarding the provision of fluoridation in Brazilian municipalities with water supply systems. Methods: Official data from the National Basic Sanitation Survey and the National Information System on Sanitation for 2017 were compared. Results: Out of 5,570 municipalities in Brazil, 4,546 (81.6%) had water supply systems. The agreement between data sources was 84%, with a Kappa of 0.668, indicating substantial agreement. However, the estimates of fluoridation provision exhibited an average discrepancy of 8.1 percentage points, ranging from 1.2 points in the Central-West region to 21.4 points in the Northeast region. Conclusion: To address these inconsistencies, it is essential to enhance information sources, ensuring more reliable data for health, sanitation authorities, and society at large.